Notch3 Is Necessary for Blood Vessel Integrity in the Central Nervous System - Henshall, Tanya L.; Keller, Annika; He, Liqun; Johansson, Bengt R.; Wallgard, Elisabet; Raschperger, Elisabeth; Mäe, Maarja Andaloussi; Jin, Shaobo; Betsholtz, Christer; Lendahl, Urban (Arteriosclerosis, thrombosis, and vascular biology, 2015)
OBJECTIVE—Vascular smooth muscle cells (VSMC) are important for contraction, blood flow distribution, and regulation of blood vessel diameter, but to what extent they contribute to the integrity of blood vessels and blood–brain barrier function is less well understood. In this report, we explored the impact of the loss of VSMC in the Notch3 mouse on blood vessel integrity in the central nervous system. APPROACH AND RESULTS—Notch3 mice showed focal disruptions of the blood–brain barrier demonstrated by extravasation of tracers accompanied by fibrin deposition in the retinal vasculature. This blood–brain barrier leakage was accompanied by a regionalized and patchy loss of VSMC, with VSMC gaps predominantly in arterial resistance vessels of larger caliber. The loss of VSMC appeared to be caused by progressive degeneration of VSMC resulting in a gradual loss of VSMC marker expression and a progressive acquisition of an aberrant VSMC phenotype closer to the gaps, followed by enhanced apoptosis and cellular disintegration in the gaps. Arterial VSMC were the only mural cell type that was morphologically affected, despite Notch3 also being expressed in pericytes. Transcriptome analysis of isolated brain microvessels revealed gene expression changes in Notch3 mice consistent with loss of arterial VSMC and presumably secondary transcriptional changes were observed in endothelial genes, which may explain the compromised vascular integrity. CONCLUSIONS—We demonstrate that Notch3 is important for survival of VSMC, and reveal a critical role for Notch3 and VSMC in blood vessel integrity and blood–brain barrier function in the mammalian vasculature.